2022
DOI: 10.3390/v14061227
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Green Tea Components against Grouper Iridovirus Infection In Vitro and In Vivo

Abstract: (1) Background: Singapore grouper iridovirus (SGIV) can cause extensive fish deaths. Therefore, developing treatments to combat virulent SGIV is of great economic importance to address this challenge to the grouper aquaculture industry. Green tea is an important medicinal and edible plant throughout the world. In this study, we evaluated the use of green tea components against SGIV infection. (2) Methods: The safe working concentrations of green tea components were identified by cell viability detection and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Catechins are active compounds that have been isolated and identified from green tea [ 35 ]. The most abundant catechins, such as EGCG and ECG, have excellent antiviral effects against influenza virus and human immunodeficiency virus (HIV) [ 36 , 37 ], and EGCG has effects against hepatitis virus, herpes viruses, and Singapore grouper iridovirus (SGIV) [ 9 , 38 , 39 ]. We previously explored the antiviral effects of some green tea extracts against SGIV and found that EGCG could combat SGIV infection with high inhibition (98.31%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catechins are active compounds that have been isolated and identified from green tea [ 35 ]. The most abundant catechins, such as EGCG and ECG, have excellent antiviral effects against influenza virus and human immunodeficiency virus (HIV) [ 36 , 37 ], and EGCG has effects against hepatitis virus, herpes viruses, and Singapore grouper iridovirus (SGIV) [ 9 , 38 , 39 ]. We previously explored the antiviral effects of some green tea extracts against SGIV and found that EGCG could combat SGIV infection with high inhibition (98.31%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants contain a variety of active ingredients. Compared with chemical drugs, some medicinal plants have advantages such as lower toxicity, fewer side effects, and less resistance to pathogens [ 8 , 9 ]. The antiviral activity of polyphenols, the main ingredient of green tea, is well known [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG) is the main catechin in tea leaves, representing 50-80% of total catechins and the most biologically active compound among other polyphenols found in tea (Kim et al 2014 ; Singh et al 2011 ; Yan et al 2020 ). Inclusion of tea catechins in aquaculture showed positive results in growth performance, antibacterial, immunostimulant, antiviral, and antioxidant activities, among others (Ji et al 2018 ; Li et al 2022 ; Qian et al 2021 ; Thawonsuwan et al 2010 ; Wang, Sun, and Zhu 2017 ; Zhang et al 2020 ; Zhang et al 2021 ). However, tea polyphenols have disadvantages, as they exhibit low stability in biological media; they are easily degraded by physiologically relevant temperature, oxygen concentration, and metal ion content at alkaline and neutral pH as well (Jin et al 2022a ; Krupkova et al 2016 ; Xu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has won honors such as the China International Tea Expo Gold Award and the China Excellent Tea Regional Public Product Brand [8]. After research, it has been confirmed that Yongchuan Xiuya not only has the functions of protecting the heart [9], anticancer [10], antioxidant [11], and antiviral [12], but also has good gastric injury prevention effects [13], DPPH free radical scavenging ability [14], and constipation prevention effects [15]. Therefore, Yongchuan Xiuya is deeply loved by consumers and has become a daily drink that people cannot put down; therefore, it is urgent to evaluate Yongchuan Xiuya tea quality.…”
Section: Introductionmentioning
confidence: 99%